Serum VEGF and ANGPT1 as angiogenesis markers may predict the outcomes of older adults with hip fractures - Yao, Yuan; Xing, Yachang; Zhao, Zhibang; Fan, Wenliang; Chu, Qingbo (Frontiers in Medicine, 2025)
ObjectiveThis study aims to investigate the potential of serum Vascular Endothelial Growth Factor (VEGF) and Angiopoietin 1 (ANGPT1) as angiogenesis markers to predict the outcomes of older adults with hip fractures.MethodsAn observational study was conducted at the Emergency Trauma Center of Nanyang Second People’s Hospital. Serum VEGF and ANGPT1 were measured on the first morning after surgery. Patients were followed up for 1 year to assess survival status and the ability to walk freely at 3, 6, and 12 months post-surgery. Receiver operating characteristic (ROC) curves were constructed to determine the predictive power of these markers, and propensity score matching (PSM) was performed to account for confounding factors. Multivariate Cox regression and logistic regression models were used to further analyze the prognostic roles of these markers.ResultsThe study cohort included 380 patients, with a mean age of 75.71 ± 8.58 years and a mortality rate of 17.11% within 1 year. Kaplan–Meier survival analysis revealed that low levels of VEGF and ANGPT1 were significantly associated with decreased survival probability. Multivariate Cox regression models indicated that low VEGF and ANGPT1 were independent risk factors for one-year mortality, while ANGPT2 did not show significant prognostic value.ConclusionElevated serum levels of VEGF and ANGPT1 are associated with improved outcomes in older adults with hip fractures, highlighting the importance of angiogenesis in fracture healing.